The African Slave Trade and Modern Household Finance. Issue 630 (21st February 2020) - Levine, Ross; Lin, Chen; Xie, Wensi
Abstract: We evaluate the impact of the African slave trade between 1400 and 1900 on modern household finance. Exploiting cross-country and cross-ethnic group differences in the intensity with which people were enslaved and exported from Africa, we find that slave exports during the 1400–1900 period are negatively associated with current measures of household (a) access to financial services, (b) access to credit, (c) use of mobile finance and (d) trust in financial institutions, suggesting that the slave trade has had an enduring, deleterious effect on household finance.